2020
DOI: 10.1080/17476348.2020.1730180
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy of Oseltamivir-Azithromycin combination therapy in prevention of Influenza-A (H1N1)pdm09 infection complications and rapidity of symptoms relief

Abstract: Objectives: This study aimed to assess the efficacy of oseltamivir-Azithromycin combination therapy for prevention of Influenza-A (H1N1)pdm09 infection associated complications and early relief of influenza symptoms. Methods: In a retrospective observational cohort study, Influenza-A (H1N1)pdm09 infection hospitalized patients were identified and divided into two groups based on the initial therapy. Group-AV patients were initiated on Oseltamivir without any antibiotic in treatment regimen while Group-AV+AZ pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…It binds to the 50S subunit of the bacterial ribosome, thus inhibiting translation of mRNA [72]. Previously, azithromycin has been used as adjunctive therapy to provide antibacterial coverage and potential immunomodulatory and anti-inflammatory effects in the treatment of some viral respiratory tract infections (e.g., influenza) [73,74]. Currently, many trials are testing the effect of azithromycin conjunction with hydroxychloroquine on the course of disease in people with SARS-CoV-2.…”
Section: Azithromycinmentioning
confidence: 99%
“…It binds to the 50S subunit of the bacterial ribosome, thus inhibiting translation of mRNA [72]. Previously, azithromycin has been used as adjunctive therapy to provide antibacterial coverage and potential immunomodulatory and anti-inflammatory effects in the treatment of some viral respiratory tract infections (e.g., influenza) [73,74]. Currently, many trials are testing the effect of azithromycin conjunction with hydroxychloroquine on the course of disease in people with SARS-CoV-2.…”
Section: Azithromycinmentioning
confidence: 99%
“…Total cumulative ARI score (range: 0-24) along with improvement in each of 8 symptoms score on daily basis were analyzed and compared for both group patients of influenza-A (non-H1N1) and influenza-B. 8 Statistical analysis. Continuous variables such as age, weight, and so forth were mentioned in tables and results as mean value plus/minus standard deviation values and univariate analysis was performed using Mann-Whitney-U test/unpaired student T-test.…”
Section: Methodsmentioning
confidence: 99%
“…Oseltamivir treatment has been proven effective in recovering from influenza illness both in terms of duration and severity in uncomplicated influenza patients. 8 Previously random clinical trials have reported that the duration of symptoms were reduced by approximately one day if oseltamivir was initiated within 48 hours of influenza symptoms onset. 3 One of the characteristics of influenza infection is the elevated levels of pro-inflammatory cytokines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies assessing the effectiveness of azithromycin when added to oseltamivir in patients with influenza showed evidence of clinical benefit ( 58 , 59 ). Conversely, analysis of a retrospective multicenter cohort of patients with MERS treated with macrolides found no improvement in 90-day mortality or viral clearance ( 60 ).…”
Section: Promoters Of the Innate Antiviral Responsementioning
confidence: 99%